Genta (Generasi Cinta Alam) Program Based on Project-Based Learning on the Development of Basic Literacy Skills in Early Childhood - Ni Kadek Mira Pradnyaswari; Didith Pramunditya Ambara; Dewi Anzelina (International Journal of Language and Literature, 2025)
Obstacles to the development of basic literacy in early childhood remain a concern, especially because educators struggle to improve children's literacy skills optimally. This condition indicates the need to implement innovative learning strategies that provide active, meaningful learning experiences for children. This study aims to determine the effect of the Genta Program (Generasi Cinta Alam) based on Project-Based Learning on the development of basic literacy in early childhood. This study uses a quantitative, quasi-experimental research design with a One-Group Pretest-Posttest Design. The research subjects were children in group A aged 4–5 years, totaling 10 students. The data collection method used a non-test method, namely observation, with an observation sheet, for the development of basic literacy. Data analysis was carried out using inferential statistics to test the research hypothesis. The study found an increase in the development of basic literacy after the implementation of the Genta Program, based on Project-Based Learning, and a significant influence on children's literacy skills. Thus, it can be concluded that the Genta Program, based on Project-Based Learning, affects the development of basic literacy in early childhood. The implications of this study indicate that project-based learning can serve as an alternative learning innovation to support children's literacy development.